Perbandingan Rata-Rata Densitas Pada Hasil Foto Thorax Proyeksi Antero Posterior (AP) Supine dan Duduk Tegak - Ali Amroji; Raditya Faradina Pratiwi; Agnes Adriana (JRI (Jurnal Radiografer Indonesia), 2019)
Background: This research aims for knowing the differences of the average density thorax photo in position AP Supine and AP of Sitting Position. In the AP projections Supine and AP sit upright will get an average density that is not significant and affect the quality of the image to be not optimal. So that further efforts are needed so that the use of the AP projection sits upright to obtain an optimal picture quality such as the use of the AP projections Supine (Firdausy, 2011) Methods: This Scientific research is quantitative with evaluating the average differences on the four points. First patient's sample did four photos, meanwhile the second patients only done with two photos. The density Measurement using densitometry, this Measurement is for knowing the average point from evert photo and exposure factor changes using certain formula and later on will be compared the first photo until the last photo. Creating percentage for the increased mAs value on the Thorax Projection of the sitting position. Results: This research shows that Thorax Projection AP of Sitting position can be combined with the average density with the photos of the Thorax Projection AP Supine Conclusions: This research shows, a significant difference in average density was obtained between the images of the AP Supine Projection and the AP Sit Upright. The average density value in the AP Supine Radiograph is greater than the AP Seated Upright and to produce an average density that is almost the same for the AP supine projection with FFD 100 cm and the AP projection sitting upright with FFD 150 it is necessary to add an mAs value of 50% to the AP projection sits upright from the mAs value used in the supine AP projection